Prevalence and pattern of dyslipidemia in an Egyptian children and adolescents with type 1 diabetes - Hend Soliman; Amany Ibrahim (SpringerOpen, 2021)
Abstract Background Hyperglycemia and dyslipidemia are commonly found metabolic abnormalities in diabetic children and adolescents and both increase the risk of cardiovascular disease. This study aimed to assess the prevalence and the pattern of dyslipidemia in Egyptian children and adolescents with type 1 diabetes (T1DM) and determine its relation with the glycemic control. Results This retrospective study included 806 children and adolescents with T1DM; 358 (44.42%) males and 448 (55.58%) females. Their mean age was 11.71 ± 3.6 years. Clinical and laboratory data were recruited from patients' files. Laboratory data include the most recent fasting lipid profile (triglycerides (TG), total cholesterol (TC), high-density lipoprotein (HDL) and low-density lipoprotein (LDL)), and the mean glycosylated hemoglobin (HbA1c) levels over the preceding year presented in percentage were calculated. Dyslipidemia in children and adolescents with T1DM represented 70.47% (568 patients). No statistically significant differences were detected between patients with and without dyslipidemia. As regards the pattern of dyslipidemia, high LDL and low HDL were the most frequent abnormalities in the study group; 62.16%, 60.21%, respectively. Patients with poor glycemic control (HbA1c > 7.5%) represent 73.45% and they were significantly older, with longer diabetes duration and higher TC, TG, and LDL compared to patients with good glycemic control. Significant positive correlations were found between HbA1c, TG, TC, and LDL with the age and diabetes duration. Conclusion We detected high prevalence of dyslipidemia in children and adolescents with T1DM. Therefore, dyslipidemia should be screened for in earlier ages in Egyptian children and adolescents suffering from T1DM. Programs directed to the prevention of dyslipidemia should be conducted, particularly for this group, in order to prevent/delay cardiovascular complications related to dyslipidemia. Also, parents should receive proper education targeting the prevention, control, and care of their diabetic children with dyslipidemia.